1999
DOI: 10.1038/sj.onc.1202659
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/MMAC1 mutations in hepatocellular carcinomas

Abstract: Mutations in the PTEN/MMAC1 gene have been identi®ed in several types of human cancers and cancer cell lines, including brain, endometrial, prostate, breast, thyroid, and melanoma. In this study, we screened a total of 96 hepatocellular carcinoma (HCC) samples from Taiwan, where HCC is the leading cancer in males and third leading cancer in females, for mutations in the PTEN/MMAC1 gene. Complete sequence analysis of these samples demonstrated a missense mutation in exon 5 (K144I) and exon 7 (V255A) from HCC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 28 publications
2
76
0
Order By: Relevance
“…3 Both a novel silent mutation in exon 5 and a putative splice mutation in intron 3 have been reported recently in the PTEN gene from human hepatocellular carcinoma (HCC), one of the most common malignancies in the world. 10 These mutations were absent in the control normal population suggesting that PTEN might be involved in hepatocarcinogenesis and that detection of PTEN mutations may be valuable as biomarker of HCC risk. 10 So far, most of the studies using immunohistochemistry for PTEN detection concluded that the expression of the protein is usually down-regulated in cancerous tissues in comparison to their normal counterparts.…”
Section: Univariate and Multivariate Analysis Of Several Clinicopathomentioning
confidence: 99%
See 1 more Smart Citation
“…3 Both a novel silent mutation in exon 5 and a putative splice mutation in intron 3 have been reported recently in the PTEN gene from human hepatocellular carcinoma (HCC), one of the most common malignancies in the world. 10 These mutations were absent in the control normal population suggesting that PTEN might be involved in hepatocarcinogenesis and that detection of PTEN mutations may be valuable as biomarker of HCC risk. 10 So far, most of the studies using immunohistochemistry for PTEN detection concluded that the expression of the protein is usually down-regulated in cancerous tissues in comparison to their normal counterparts.…”
Section: Univariate and Multivariate Analysis Of Several Clinicopathomentioning
confidence: 99%
“…9 Although PTEN mutations and allele loss at 10q23 have been reported to occur in HCC with a high frequency (30 -50%), the prognostic significance of PTEN mutation for HCC-patients remains a matter of controversy. 10 Different studies suggest that PTEN negatively regulates carcinoma cell growth by controlling Akt/PKB signaling pathway 11 whereas Akt/PKB can induce iNOS and COX II expression. 12 It has been shown recently that PI3K/Akt signaling pathway is involved in HCC 13 and that iNOS and COX II are factors with well established implication in hepatocarcinogenesis especially among HCV-positive and cirrhotic patients.…”
mentioning
confidence: 99%
“…Loss of this important tumor suppressor gene product, which modulates PI3K activity, occurs in a variety of human neoplasms (Steck et al, 1997). Mutational inactivation of PTEN has been detected in human HCC (Fujiwara et al, 2000;Yao et al, 1999;Yeh et al, 1999). Another phosphoinositide-speci®c phosphatase SHIP has been described (Lioubin et al, 1996;Dame et al, 1996).…”
Section: Roles Of Pi3k-mediated Nf-kb Activation Pathway In Hepatocarmentioning
confidence: 99%
“…During initiation and progression of HCC, tumor-suppressor genes such as p53 (Li et al, 1993), p16, p21 (Qin et al, 1998), p27 (Tannapfel et al, 2000), beta-catenin (Wong et al, 2001), PTEN (Yao et al, 1999), and Rb were frequently deregulated or completely disrupted by point mutations, loss of heterozygosity (LOH), and methylation. On the other hand, oncogenes and certain cell cycle controllers, such as c-myc (Wu et al, 1996), c-Jun, c-fos (Twu et al, 1993), c-met (Boix et al, 1994;Grigioni et al, 1995), cets-1 (Ozaki et al, 2000), cyclin D1 (Peng et al, 1998;Deane et al, 2001;Joo et al, 2001), cyclin E (Peng et al, 1998), and gankyrin (Higashitsuji et al, 2000), were overexpressed or re-expressed in the later stage of hepatocellular carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%